Identification of the Genes of the Plant Pathogen Pseudomonas syringae MB03 Required for the Nematicidal Activity Against Caenorhabditis elegans Through an Integrated Approach - Ali, Muhammad; Gu, Tong; Yu, Xun; Bashir, Anum; Wang, Zhiyong; Sun, Xiaowen; Ashraf, Naeem Mahmood; Li, Lin (Frontiers in Microbiology, 2022)
Nematicidal potential of the common plant pathogen Pseudomonas syringae has been recently identified against Caenorhabditis elegans. The current study was designed to investigate the detailed genetic mechanism of pathogenicity by applying comparative genomics, transcriptomics, mutant library screening, and protein expression. Results showed that P. syringae strain MB03 killed C. elegans in the liquid assay by gut colonization. The genome of P. syringae MB03 was sequenced and comparative analysis including multi locus sequence typing, mean amino acid identity, and genome-to-genome distance placed MB03 in phylogroup II of P. syringae. Furthermore, comparative genomics of MB03 with nematicidal strains of Pseudomonas aeruginosa (PAO1 and PA14) predicted 115 potential virulence factors in MB03. However, genes for previously reported nematicidal metabolites, such as phenazine, pyochelin, and pyrrolnitrin, were absent in the MB03 genome. Transcriptomics analysis showed that the growth phase of the pathogen considerably affected the expression of virulence factors, as genes for the flagellum, glutamate ABC transporter, phoP/phoQ, fleS/fleR, type VI secretion system, and serralysin were highly up-regulated when stationary phase MB03 cells interacted with C. elegans. Additionally, screening of a transposon insertion mutant library led to the identification of other nematicidal genes such as acnA, gltP, oprD and zapE. Finally, the nematicidal activity of selected proteins was confirmed by heterologous expression in Escherichia coli.